Disinfection 2018
DOI: 10.5772/intechopen.76340
|View full text |Cite
|
Sign up to set email alerts
|

Carrier and Liquid Heat Inactivation of Poliovirus and Adenovirus

Abstract: Viral inactivation is typically studied using virus suspended in liquid (liquid inactivation) or virus deposited on surfaces (carrier inactivation). Carrier inactivation more closely mimics disinfection of virus contaminating a surface, while liquid inactivation mimics virus inactivation in process solutions. The prevailing opinion has been that viruses are more susceptible to heat inactivation when suspended in liquid than when deposited on surfaces. In part, this reflects a paucity of comparative studies per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The authors reported that the parvovirus was more readily inactivated in suspension than in the lyophilized state with higher residual moisture (2%), while longer heating times were required for inactivation of the virus in lyophilized materials with lower moisture content (1%). In our own studies [8] with poliovirus type 1 and adenovirus type 5, the D values measured at 46°C displayed the greatest difference between the surface and suspension inactivation approaches, with values ranging from 14. What exactly determines the shape of the D vs. temperature curve?…”
Section: Herpes Simplex Virus Typementioning
confidence: 71%
See 4 more Smart Citations
“…The authors reported that the parvovirus was more readily inactivated in suspension than in the lyophilized state with higher residual moisture (2%), while longer heating times were required for inactivation of the virus in lyophilized materials with lower moisture content (1%). In our own studies [8] with poliovirus type 1 and adenovirus type 5, the D values measured at 46°C displayed the greatest difference between the surface and suspension inactivation approaches, with values ranging from 14. What exactly determines the shape of the D vs. temperature curve?…”
Section: Herpes Simplex Virus Typementioning
confidence: 71%
“…Prevailing opinion is that viruses are less susceptible to heating when dried on surfaces than when suspended in solutions, and that dry heat efficacy is related to residual moisture or relative humidity [22][23][24][25][26]. As mentioned previously, there are only relatively few studies [8,25] that have actually evaluated thermal inactivation on surfaces and in suspension in a side-by-side study design. There are a number…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations